Cultural Policy and Cultural Life: Québec’s Experience (AmeriQuests, 2012)
The object of this article is draft a brief history of cultural policymaking in Québec through various initiatives adopted by successive governments in the largely French-speaking province since the middle of the 20th century. These initiatives have been instrumental in the development of an amazingly rich and diversified cultural life within Québec.